An integrated high-throughput microfluidic circulatory fluorescence-activated cell sorting system (μ-CFACS) for the enrichment of rare cells. Issue 16 (21st July 2021) - Cai, Kunpeng; Mankar, Shruti; Ajiri, Taiga; Shirai, Kentaro; Yotoriyama, Tasuku
Abstract : A fully integrated high-throughput microfluidic circulatory fluorescence-activated cell sorting (μ-CFACS) system has been constructed for the contamination-free enrichment of rare cells in clinical environments. Abstract : There is an increasing need for the enrichment of rare cells in the clinical environments of precision medicine, personalized medicine, and regenerative medicine. With the possibility of becoming the next-generation cell sorters, microfluidic fluorescence-activated cell sorting (μ-FACS) devices have been developed to avoid cross-contamination, minimize device footprint, and eliminate bio-aerosols. However, due to highly precise flow control, the achievable throughput of the μ-FACS system is generally lower than the throughput of conventional FACS devices. Here, we report a fully integrated high-throughput microfluidic circulatory fluorescence-activated cell sorting (μ-CFACS) system for the enrichment of clinical rare cells. A microfluidic sorting cartridge has been developed for enriching samples through a sequential sorting process, which was further realized by the integration of both fast amplified piezoelectrically actuated on-chip valves and compact pneumatic cylinders actuated on-chip valves. At an equivalent throughput of ∼8000 events per second (eps), the purity of rare fluorescent microparticles has been significantly increased from ∼0.01% to ∼27.97%. An enrichment of ∼9400-fold from 0.009% to 81.86% has also been demonstrated for isolating fluorescently labelled MCF-7 breast cancer cells from Jurkat cells at an equivalent sorting throughput of ∼6400 eps. With the advantages of high throughput and contamination-free design, the proposed integrated μ-CFACS system provides a new option for the enrichment of clinical rare cells.